Reducible PEG-POD/DNA Nanoparticles for Gene Transfer In Vitro and In Vivo: Application in a Mouse Model of Age-Related Macular Degeneration - Bhanu Chandar Dasari; Siobhan M. Cashman; Rajendra Kumar-Singh (Elsevier, 2017)
Non-viral gene delivery systems are being developed to address limitations of viral gene delivery. Many of these non-viral systems are modeled on the properties of viruses including cell surface binding, endocytosis, endosomal escape, and nuclear targeting. Most non-viral gene transfer systems exhibit little correlation between in vitro and in vivo efficiency, hampering a systematic approach to their development. Previously, we have described a 3.5 kDa peptide (peptide for ocular delivery [POD]) that targets cell surface sialic acid. When functionalized with polyethylene glycol (PEG) via a sulfhydryl group on the N-terminal cysteine of POD, PEG-POD could compact plasmid DNA, forming 120- to 180-nm homogeneous nanoparticles. PEG-POD enabled modest gene transfer and rescue of retinal degeneration in vivo. Systematic investigation of different stages of gene transfer by PEG-POD nanoparticles was hampered by their inability to deliver genes in vitro. Herein, we describe functionalization of POD with PEG using a reducible orthopyridyl disulfide bond. These reducible nanoparticles enabled gene transfer in vitro while retaining their in vivo gene transfer properties. These reducible PEG-POD nanoparticles were utilized to deliver human FLT1 to the retina in vivo, achieving a 50% reduction in choroidal neovascularization in a murine model of age-related macular degeneration. Keywords: nanoparticles, age-related macular degeneration, PEGylation, cell penetrating peptide, gene transfer, reducible particles, laser-induced choroidal neovascularization